Thyroid Function and Renal Biomarker Correlation in Euthyroid and Hypothyroid Pregnant Women: A Comparative Analysis - R Shah, Saiqa; Parwez, Anjum; Mishra, Rashmi; Khan, M.M.; Afaq, Nashra; Shadman, Syed; Sodhi, Harvir Singh (Journal of Neonatal Surgery, 2025)
Introduction: Thyroid dysfunction, particularly hypothyroidism, is a prevalent endocrine disorder during pregnancy that significantly affects maternal and fetal health. Thyroid hormones also influence renal physiology, making the assessment of renal markers crucial in hypothyroid pregnancies. Objectives: To estimate serum creatinine levels in euthyroid and hypothyroid pregnant women and assess their correlation with thyroid-stimulating hormone (TSH). Methods: A cross-sectional comparative study was conducted among 200 pregnant women, comprising 100 newly diagnosed hypothyroid (cases) and 100 euthyroid (controls), aged 20–40 years. TSH was measured using electro-chemiluminescence (Cobas e411), and serum creatinine was assessed by the Modified Jaffe’s method. Statistical analysis was done using SPSS v20.0. Results: Mean serum TSH was significantly lower in hypothyroid cases (1.32 ± 0.89 μIU/ml) compared to controls (2.28 ± 0.91 μIU/ml, p = 0.002). Mean serum creatinine was significantly higher in cases (0.87 ± 0.41 mg/dl) versus controls (0.55 ± 0.17 mg/dl, p = 0.001). A significant correlation was found between TSH and serum creatinine levels in hypothyroid patients. Conclusion: Hypothyroidism in pregnancy is associated with elevated serum creatinine, indicating renal function impairment. Regular monitoring of thyroid and renal parameters is essential for optimal maternal and fetal outcomes